PERSEPSI MASYARAKAT TERHADAP LARANGAN PERNIKAHAN PADA BULAN SURO DALAM ADAT JAWA DI DESA RUMBAI JAYA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Lestari, Ayu; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the beliefs of the ancestors of Rumbai Jaya Village people who are hereditary that is still believing in the existence of bad dates and full of bad luck (disadvantaged), namely dating in the month of Suro so that many people avoid the month of Suro when they will implement the month of Suro major events including weddings. This research formulated the problem in